A new way of concentrating the cellular material of exudates - M. G. Leonov; V. I. Novik; S. A. Belyaeva; Ya. H.-B. Ershova; Zh. P. Selifonova (Медицинский совет, 2018)
Objective. Improve the method for concentrating the cellular material of serous cavities exudates for cytological investigation.Materials and methods. The optimal time of accumulation of cell samples in effusion liquids was determined on the basis of the sedimentation method using a dropping funnel by examining 28 samples of exudates (pleural and abdominal) obtained from 24 patients with ovarian cancer. The two methods for concentrating the cellular material of exudate were compared: the method using a dropping funnel and the method using a cylinder.Results. It was found that the 60-minute exposure time was optimal in using a dropping funnel to concentrate the cellular material of exudates.Conclusion. Using a dropping funnel to concentrate the cellular material of the exudates is optimal. In this case, the investigational preparations contain a sufficient amount of cellular material for the cytological study and the cell complexes are larger than those in using the cylinder.